골드 나노구조체 제조에 의한 표면 플라즈몬 공명 감도 증가 및 면역 센서로의 응용 - 송영아 (The Graduate School, Ajou University, 2010)
Surface Plasmon Resonance (SPR) has attracted considerable attention owing to their promising application as non-labeling biomolecular detection. Recently, for sensitivity enhancement in the SPR detection, attempts of using surface plasmon have been performed after fabrications of nanostructures instead of using flat films. This study aims to manufacture a highly sensitive SPR chip with Localized surface Plasmon (LSP) from Au nanostructures at regular intervals and apply it as a sensor for measuring the concentration of alcohol. The periodic nanostructured SPR chip can be produced by using a film of silica particles with hundreds of nanometer size as a template and evaporating Au on it. A method of using a nano- or micro- particle as a template and producing a nano-metal structure has much been studied by P. Van Duyne. He used a Nano Sphere Lithography (NSL) to produce it into a mono layer by spin coating and evaporated metal on it. Formation of a particle layer by spin coating has the disadvantage of non guaranteeing thickness control and uniformity on the substrate. In order to make well-ordered Au nanostructures on SPR sensor chip, thin films of hexagonally close packed (hcp) silica nanoparticles with average sizes of 300 ± 7 nm or 150 ± 4 nm were deposited on a glass substrate by the Langmuir Blodgett (LB) technique and used as the template. It is reported that LB technique takes advantage of high reproducibility, large area films formation, mass production capability at low cost. To generate nanostructures, Au with 20 nm thickness was evaporated on the LB monolayer of silica particles by using an E-beam evaporation technique. After Au deposited into the voids of silica particle hcp film, the nanostructures were obtained by the removal of colloidal film. The size and close packing of silica colloids on the substrate were measured by scanning electron microscope (SEM). Also, we obtained periodic triangular pyramidal Au nanostructures on Au SPR chip. In addition, the protein-protein interaction was observed using anti-hIgG and hIgG to evaluate application of SPR chip.
학위논문(석사)--아주대학교 일반대학원 :분자과학기술학과,2010. 2
Keywords: 골드 나노구조체; 표면 플라즈몬; 면역 센서